Social network analysis of obsidian artefacts and Māori interaction in northern Aotearoa New Zealand - Ladefoged, Thegn N. (PLoS One, 2019)
Over the span of some 700 years the colonizing populations of Aotearoa New Zealand grew, with subsequent changes in levels of interaction and social affiliation. Historical accounts document that Māori society transformed from relatively autonomous village-based groups into larger territorial lineages, which later formed even larger geo-political tribal associations. These shifts have not been well-documented in the archaeological record, but social network analysis (SNA) of pXRF sourced obsidian recovered from 15 archaeological sites documents variable levels of similarity and affiliation. Three site communities and two source communities are defined based on the differential proportions of obsidian from 13 distinct sources. Distance and travel time between archaeological sites and obsidian sources were not the defining factors for obsidian source selection and community membership, rather social considerations are implicated. Some archaeological sites incorporated material from far off sources, and in some instances geographically close sites contained material from different sources and were assigned to different communities. The analytical site communities constitute relational identifications that partially correspond to categorical identities of current Māori iwi (tribal) territories and boundaries. Based on very limited temporal information, these site communities are thought to have coalesced sometime after AD 1500. By incorporating previously published and unpublished data, the SNA of obsidian artefacts defined robust network communities that reflect differential levels of Māori interaction and affiliation.